Układy wielogałęziowe rurociągów energetycznych - GARDIAS, Piotr; KRECZMAR, Antoni; TESSAROWICZ, Michał (Engineering Transactions, 1970)
Multibranch and multinodal systems of power pipelinesThis paper presents theoretical considerations which utilize the approximate analytical method (the influence of components of the moment on the angular deformation of the arcs around the axis of perpendiculars to the corresponding component being disregarded) for solving systems of multibranch and multinodal pipelines with elements arbitrarily situated in space.The relationships which solve these systems are presented, and the concepts introduced are discussed in the relation to the matrix of incidence, which defines their structure. Further given are the formulae determining the magnitude of the forces, moments, linear and angular displacements and the reduced stresses at any point of the pipeline.On the basis of the guidelines presented in this paper, programmes were carried out for the computer GIER, on the basis of which calculations are performed for the power pipelines. These programmes are in the possession of the Design Offices of the United Heavy Machine Construction Industries in Warsaw and the Institute of